Constructing a 'first' First Lady through memory: The case of China's Peng Liyuan. (September 2018) - Ling, Qi; Berkowitz, Dan
Our study analyzed how cultural memory of previous and contemporary First Ladies was used as a journalistic device by US media to make sense of the unusual case of Peng Liyuan, the current First Lady of China. A textual analysis showed that news coverage of Peng relied on a Western and gendered conception of the First Lady while distancing her from her predecessors. We found that resonance with the idealized First Lady template served to signal Peng's progressiveness in both the general and the political sense. Although Peng's performance as a 'first' First Lady was celebrated in international politics, it is important to be aware that cultural values and gender norms associated with the First Lady identity can become rhetorical tools that sustain the existing political order between the West and the non-West.